2001
DOI: 10.1046/j.0022-202x.2001.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interleukin-4 in the Epidermis of Transgenic Mice Results in a Pruritic Inflammatory Skin Disease: An Experimental Animal Model to Study Atopic Dermatitis

Abstract: Atopic dermatitis, a common, chronic, inflammatory skin disease that occurs with increasing prevalence, is characterized by hyperactivated cytokines of helper T cell subset 2 and is frequently associated with staphylococcal infection. An experimental animal model of atopic dermatitis induced by transgenically introduced cytokine is not available. We generated a transgenic mouse line expressing epidermal interleukin-4, a critical cytokine of helper T cell subset 2. Here we show that transgenic mice spontaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
221
2
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(234 citation statements)
references
References 25 publications
(41 reference statements)
7
221
2
4
Order By: Relevance
“…Basophils produce large amounts of IL-4 after FcRI ligation (Sullivan et al, 2011), and overexpression of IL-4 is sufficient to drive eosinophilic skin inflammation (Chan et al, 2001). Although sensitized and DNFB-challenged C57BL/6 IL-4 +/ mice developed tissue eosinophilia comparable with wildtype mice, IL-4 / mice (KN2/KN2) had no eosinophil accumulation (Fig.…”
Section: Basophil-derived Il-4 Regulates Eosinophil Entry Into the Skinmentioning
confidence: 99%
“…Basophils produce large amounts of IL-4 after FcRI ligation (Sullivan et al, 2011), and overexpression of IL-4 is sufficient to drive eosinophilic skin inflammation (Chan et al, 2001). Although sensitized and DNFB-challenged C57BL/6 IL-4 +/ mice developed tissue eosinophilia comparable with wildtype mice, IL-4 / mice (KN2/KN2) had no eosinophil accumulation (Fig.…”
Section: Basophil-derived Il-4 Regulates Eosinophil Entry Into the Skinmentioning
confidence: 99%
“…It has been reported that skin of transgenic mice over-expressing IL-4 developed lesions, suggesting that IL-4 may be critical for development of skin lesions (Chan et al 2001). Accordingly, the current study also analyzed mRNA expression of T H 2 cytokines in skin (and intestine) and found elevated levels of IL-4, IL-5 and IL-13 in both sites of EC as well as orally-treated mice.…”
Section: Discussionmentioning
confidence: 83%
“…An epidermal IL-4etrans-genic mouse model was developed that closely resembles human AD clinically, histopathologically, serologically, bacteriologically, and immunologically. [138][139][140][141] The dermal blood vessels in this mouse model show changes consistent with angiogenesis, including elongation, sprouting, and intussusception. 142 Chen et al 143 recently noted a progressive increase in blood vessel number, diameter, and percent dermal area occupied by CD31 1 and VEGFR2 vessels as the disease evolves from start to a chronic state.…”
Section: Rosaceamentioning
confidence: 73%